(untitled) (Research, Society and Development, 2022)
This research had as purpose to use the SWOT matrix as an analysis tool to subsidize the possibility of creating an intercity consortium on gestating and managing the Urban Solid Waste (USW) on the Baixa Mogiana microregion, Minas Gerais (MG). It was made a bibliographic survey and the region diagnosys happened starting from documental research and field research. From these results, the SWOT matrix technique was applied. The results indicate that: the population concentrated in the urban area that has coverage of domestic waste collection, the region has collectors of reusable and recyclabe materials as a “force”; the absence of a Sorting and Composting Plant (SCP), sanitary landfill, as well as the presence of dumpgrounds and controlled landfills configure betwen the “weaknesses”. One of the “threats” is the deflation of consorces during its planing or implementation phase. The adoption of consortiuns between municipalities comes as a viable “opportunity” as it reaches scale gains through regional measures.